Stop North Korea! a radical new approach to the North Korea standoff - Iverson, Shepherd 1956- (Tuttle Publishing, 2017)
"This radical new approach to dealing with North Korea offers a refreshing perspective on an intransigent and deadly situation. Imagine you control a multi-billion dollar capital fund, and North Korea is an underperforming corporation. You see it is undervalued and want to take it over, but it is controlled by an old-fashioned board of directors--the Kim family and a small number of ultra elites--who will not negotiate a deal. In this regressive situation it is logical to offer its shareholders--the political and military elites, government managers and bureaucrats, and the general population--a higher price for their shares to convince them to overrule their board of directors. Stop North Korea! A Radical New Approach to the North Korea Standoff applies this basic scenario to a situation that has become dire, and for which a strong positive solution is crucial. This book shows how investment rather than constraint--the carrot rather than the stick--will not only deter the North Korea threat, but enhance the global community in ways perhaps unimagined in the past"--Provided by publisher.